Henry IV, parts one and two - Shakespeare, William, 1564-1616.; Shakespeare, William, 1564-1616. (New York : SparkNotes, 2005)
Presents the original text of Shakespeare's historical tragedy, in which King Henry IV grows increasingly ill as the rebellion rages on, and his son Hal struggles with the knowledge that he will soon have to wear the crown, side-by-side with a modern version; and includes marginal notes and explanations and full descriptions of each character.
"The plays plus a translation anyone can understand"--Cover.
Young Adult
Young Adult
Keywords: Henry -- IV, -- King of England, -- 1367-1413 -- Drama; Henry -- IV, -- King of England, -- 1367-1413 -- Drama; Historical drama; Great Britain -- History -- Henry IV, 1399-1413 -- Drama; Great Britain -- History -- 1399-1485, Lancaster and York -- Drama